2021
DOI: 10.1002/adfm.202108381
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Single Atom Environmental Catalysis: Fundamentals, Applications, and Opportunities

Abstract: The development of efficient catalysts is pivotal for pollution abatement to guarantee a sustainable and green industrial production. Supported single atom catalysts (SACs) with the advantages of maximum atom utilization, unique electronic structure, and distinguished metal support interaction have recently become a hotspot in the catalysis community, and bring new opportunities for environmental catalysis. This review aims to provide a comprehensive overview of the latest progress on the environmental SACs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 342 publications
(283 reference statements)
0
41
0
Order By: Relevance
“…Ni clusters are needed for the full hydrogenation of CO 2 with the 8e − redox cycle. 35 The unique characteristics of the SAC render Ni-SAC active for electro-chemical CO 2 reduction to CO. 154–157 Frei and his co-workers 35 confirmed that the MgO supported Ni-SAC is active for RWGS. MgO supported Ni NPs are normally highly active for CO 2 methanation.…”
Section: Co2 Hydrogenation To Comentioning
confidence: 88%
“…Ni clusters are needed for the full hydrogenation of CO 2 with the 8e − redox cycle. 35 The unique characteristics of the SAC render Ni-SAC active for electro-chemical CO 2 reduction to CO. 154–157 Frei and his co-workers 35 confirmed that the MgO supported Ni-SAC is active for RWGS. MgO supported Ni NPs are normally highly active for CO 2 methanation.…”
Section: Co2 Hydrogenation To Comentioning
confidence: 88%
“…Recent cutting-edge research suggests that atomically dispersing an active metal element in another metal material, namely single-atom alloys, will efficiently tune the adsorption and catalytic properties of the active metal element. [26][27][28][29][30][31][32] Due to the unique geometry of single-atom alloys, the locations of transition states and the binding sites of reaction intermediates are oen decoupled, resulting in deviations from the scaling relationship. [33][34][35] Accordingly, developing Pt-based single-atom alloys might be an effective strategy to break the scaling relationship towards FOR-related adsorbed species and address the sluggish kinetics of Pt-based FOR electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Nevertheless, the structural uniformity of the active sites in SACs offers an atomic-scale perspective to reveal the relationship between the structure and catalytic activity. 20,21 Actually, quite a number of SACs including Ni-SA-x/ZrO 2 , 22 Er 1 /CN-NT, 23 W 18 O 49 @Co, 24 Cu SAs/UiO-66-NH 2 , 25 and Co-SA@SP-800 26 have been developed to catalyze the CO 2 photoreduction. In particular, catalysts with bimetallic active sites were revealed to be able to improve the catalytic performance of various reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Owing to the virtues of ultimate atomic utilization, tunable coordination environment, and exceptional catalytic properties, single-atomic site catalysts (SACs) have been emerging as a rising star for highly efficiently photocatalyzing CO 2 RR. , Nevertheless, the structural uniformity of the active sites in SACs offers an atomic-scale perspective to reveal the relationship between the structure and catalytic activity. , Actually, quite a number of SACs including Ni-SA-x/ZrO 2 , Er 1 /CN-NT, W 18 O 49 @Co, Cu SAs/UiO-66-NH 2 , and Co-SA@SP-800 have been developed to catalyze the CO 2 photoreduction. In particular, catalysts with bimetallic active sites were revealed to be able to improve the catalytic performance of various reactions. However, the application of atomic-pair catalysts (APCs) over CO 2 photoreduction appears to still remain unreported, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%